Editorial Vol.2(1) (The Spectrum, 2024)
EditorialThe progress of knowledge within a particular field relies on the exploration, investigation, and realization of new pathways of understanding. Identifying these novel avenues for knowledge exploration is essential in response to temporal and contextual demands. Consequently, genuine research efforts and knowledge creation must align with the exigencies of the time and the significance of their objectives.Taking inspiration from the inaugural edition of The Spectrum, this current issue strives to present more innovative ideas within the realms of social sciences and management studies. Within the humanities and social sciences domain, this edition comprises four articles, each delving into diverse topics. These range from a rhetorical analysis of Joe Biden's victory speech to a reevaluation of the history of Modern Nepali Plays. Furthermore, additional articles explore facets of popular culture such as cinema and web series.Following the journal's commitment to fostering interdisciplinary discourse, the two articles within the domain of Management Science address pivotal issues within their respective spheres. For instance, one article elucidates the factors contributing to the entrepreneurial success of women-led enterprises in the Kathmandu valley, while the other investigates the determinants of turnover within academic institutions in the same locale.Acknowledging the inherent challenges associated with pioneering new areas of study, we nonetheless aspire that our efforts will contribute to the scholarly landscape. Moving forward, we endeavor to incorporate more pressing topics into subsequent editions, recognizing that constructive feedback serves as a catalyst for improvement. Therefore, we earnestly invite critical and sincere commentary to further enhance our scholarly pursuits.The Editor